Sememe Heredity of Action Semantics: Evidence From the Priming Effect and Prospective Memory - Yu, Zhanyu; Ma, Yue; Wang, Lijuan (Frontiers in Psychology, 2020)
The sememe heredity of action semantics may be affected by the related association of a verb or noun in an action phrase and the related association between one action phrase and another. The motor encoding theory and the five-component view of the subject-performed task supported by the verb’s specificity highly promote the enactment effect. However, the episodic integration theory emphasizes the role of semantic integration between the verb and noun on the enactment effect. In this study, a subject-performed task was combined with a priming paradigm and found that verb-semantic priming quantity was more significant than that of noun-semantic priming quantity under motor encoding in Experiment 1. Besides, it was observed that the verb-semantic association might play a more significant role in the sememe heredity of action semantics. Therefore, in Experiment 2, a subject-performed task was combined with the dual task of prospective memory. Results showed that the accuracy of prospective memory targets related to the learning phrases was significantly higher compared to that of the prospective memory targets unrelated to the learning phrases. Besides, the above difference is more evident verbally compared to motor encoding conditions. Thus, the sememe heredity of action semantics may rely on the related association of action semantic contents rather than on the semantic processing form of external motor encoding.